Al Zarnuji's Learning Principles in the Malaysian National Education Philosophy: an integrated model of Islamic Spiritual Intelligence - Tengku Mohd Farid, Tengku Abdul Aziz (Center for Communication Technology and Human Development (UniMAP), 2020)
Link to publisher's homepage at https://johdec.unimap.edu.my/